Discovery of selective N-[3-(1-methyl-piperidine-4-carbonyl)-phenyl]-benzamide-based 5-HT1F receptor agonists: Evolution from bicyclic to monocyclic cores. Issue 19 (1st October 2015) - Zhang, Deyi; Blanco, Maria-Jesus; Ying, Bai-Ping; Kohlman, Daniel; Liang, Sidney X.; Victor, Frantz; Chen, Qi; Krushinski, Joseph; Filla, Sandra A.; Hudziak, Kevin J.; Mathes, Brian M.; Cohen, Michael P.; et al.
Graphical abstract: Abstract: Preclinical experiments and clinical observations suggest the potential effectiveness of selective 5-HT1F receptor agonists in migraine. Identifying compounds with enhanced selectivity is crucial to assess its therapeutic value. Replacement of the indole nucleus in2 (LY334370) with a monocyclic phenyl ketone moiety generated potent and more selective 5-HT1F receptor agonists. Focused SAR studies around this central phenyl ring demonstrated that the electrostatic and steric interactions of the substituent with both the amide CONH group and the ketone CO group play pivotal roles in affecting the adopted conformation and thus the 5-HT1F receptor selectivity. Computational studies confirmed the observed results and provide a useful tool in the understanding of the conformational requirements for 5-HT1F receptor agonist activity and selectivity. Through this effort, the 2-F-phenyl and N -2-pyridyl series were also identified as potent and selective 5-HT1F receptor agonists.